The Treatment Of Severe Arch -Tooth Length Dıscrepancy In The Early Mıxed Dentıtıon By Frankel 2 Applıance And Guıdance Of Eruptıon - İlken Kocadereli; Ayhan Enacar (Galenos Yayinevi, 1994)
The early mixed dentition period is the time of greatest opportunity for guidance of eruption and the interception of malocclusion in tooth -arch length dicrepancy cases.